2021
DOI: 10.1177/19476035211044822
|View full text |Cite
|
Sign up to set email alerts
|

The Chondrogenic Potential of First-Trimester and Term Placental Mesenchymal Stem/Stromal Cells

Abstract: Objectives Mesenchymal stem/stromal cells (MSCs) are a well-established cell source for cartilage engineering, but challenges remain as differentiation often results in chondrocyte hypertrophy. Chondrogenic potential also varies with MSC source and donor age. We assessed the chondrogenic potential of first-trimester and term placental MSCs and compared their response to commonly used bone marrow MSCs (BM-MSCs). Design MSCs were isolated from first-trimester and term placentae. BM-MSCs were commercially obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Besides, as in this study, Prideaux et al found a very large increase in Comp in cells cultured with chondrogenic medium compared to those cultured in complete medium (about 200-fold) [55]. These results agree with some studies in the literature: in a study by Joanna L. James et al, no increase in Sox9 was observed during chondrogenesis [23]. Similarly, Prideaux et al generated two cell lines capable of chondrogenic differentiation.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Besides, as in this study, Prideaux et al found a very large increase in Comp in cells cultured with chondrogenic medium compared to those cultured in complete medium (about 200-fold) [55]. These results agree with some studies in the literature: in a study by Joanna L. James et al, no increase in Sox9 was observed during chondrogenesis [23]. Similarly, Prideaux et al generated two cell lines capable of chondrogenic differentiation.…”
supporting
confidence: 92%
“…Further, MSCs are known to exert immunomodulatory and anti-inflammatory effects [17]. MSCs can be isolated from various tissues (bone marrow, adipose tissue, umbilical cord, skeletal muscle, cartilage, synovium, cardiac tissue, and dental tissue) [18][19][20][21][22] and MSCs differentiation can be influenced by the cell source [23].…”
mentioning
confidence: 99%
“…Numerous authors have concentrated their attention on the application of PRF in the tissue engineering of cartilage and tendons, which has resulted in an increase in in vitro, preclinical, and clinical research [ 14 , 19 , 20 ]. Chondrogenesis depends on several cartilage-specific markers, including collagen, aggrecan (ACAN), SRY-box transcription factor 9 (SOX9), and osteogenic-related markers, such as alkaline phosphatase (ALPL), bone gamma-carboxyglutamate protein (BGLAP), and RUNX family transcription factor 2 (RUNX2), which participate in tissue regeneration [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%